AIEgen–lipid structures: Assembly and biological applications. Issue 1 (29th December 2020) - Cao, Hongqian; Yang, Yang; Li, Junbai
Abstract: Aggregation‐induced emission (AIE) molecules possess notable advantages outperforming traditional aggregation caused quenching (ACQ) materials on various aspects. They are rapidly developed these years. More and more AIE luminogens (AIEgens) are designed to possess multifunctions such as the abilities of near‐infrared two‐photon absorption and reactive oxygen species (ROS) generation, which could be used for deep tissue imaging and photodynamic therapy. The AIEgens exhibit great potential in biological application field. However, despite the photophysics stability and ROS generation ability in aggregated states are favorable conditions, their applications in biological field are retarded by uncontrolled size, single imaging mode, low targeting efficiency, and also poor biocompatibility and dispersibility in physiological environment. The combination of AIEgen and lipid is a straightforward, promising, and intensively used way to solve the above problems. Due to the special amphipathic property of lipid, which results from a hydrophilic head and hydrophobic tail structure, there are various possibilities of combination modes between lipid and AIEgen. Even a little procedure or condition change during the synthesis process will impact the structure of obtained product, which can further influence its application. Herein, we summarize the synthesis methods of different AIEgen–lipid compounds with diverse structures and properties, as well as their biological applications in this contribution, which has not been presented before, being aimed at serving as a synthesis and application reference for these promising AIEgen–lipid compounds applied in biological region. Abstract : According to the different synthesis methods which result in various structures and properties of AIEgen‐lipids, the structures are summarized into four kinds: core‐shell, inserted, imbedded and like‐lipid structures. The AIE molecule in monodisperse state presents no emission but aggregate shows high fluorescence intensity, as well as distinct ROS generation performance.